Effect of wire size on maxillary arch force/couple systems for a simulated high canine malocclusion. Major PW, Toogood RW, Badawi HM, Carey JP, Seru S - Akan, Seden (Maney Publishing, 2014)
[Abstract Not Available]
Effect of wire size on maxillary archforce/couple systems for a simulated high canine malocclusion
Keywords: Maxillary Archforce; Couple System; Canine Malocclusion